1983
DOI: 10.1039/c39830000202
|View full text |Cite
|
Sign up to set email alerts
|

Static distortion of radical cations of cyclopropane at 4.2 K: e.s.r. evidence

Abstract: E.s.r. evidence has been obtained that cyclopropane cations exhibit a static distortion from Dgh to C2" symmetry in a matrix at 4.2 K; the 3e' (D3h) highest occupied degenerate orbital splits into 6a, and 3bl (C2") orbitals and the unpaired electron occupies 6a1, giving dominant spin densities on the two basal carbon atoms. Recentlywe have found that C2H6+, a Jahn-Teller active molecule, trapped in SF, shows a reversible temperature t Preliminary results were presented at the 46th Autumn Annual Meeting of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 0 publications
4
52
0
2
Order By: Relevance
“…The distortion to D 2h symmetry can, in fact, be detected experimentally in a matrix at low temperatures. [100] The ESR spectra of C 6 H 6 in a freon matrix indicate an increased spin density at atoms C 1 and C 4 at 4.2 K but an equivalent spin density at 100 K (Figure 19). Thus, the question arises whether the D 2h structure is static and destabilized at higher temper- Figure 19.…”
Section: Benzenementioning
confidence: 96%
“…The distortion to D 2h symmetry can, in fact, be detected experimentally in a matrix at low temperatures. [100] The ESR spectra of C 6 H 6 in a freon matrix indicate an increased spin density at atoms C 1 and C 4 at 4.2 K but an equivalent spin density at 100 K (Figure 19). Thus, the question arises whether the D 2h structure is static and destabilized at higher temper- Figure 19.…”
Section: Benzenementioning
confidence: 96%
“…Before we discuss the obtained HFI fields in Table II for individual organics, we compare our calculations with well-documented experimental data of the HFI strengths in benzene cation 22 and C 60 anion. 23 For benzene cation, the removal of one electron causes a Jahn-Teller distortion of molecular structure from D 6h to D 2h symmetry.…”
Section: A Organics Containing Only H Nuclear Spinmentioning
confidence: 99%
“…The approximate independence of the yield of on the chain length suggests that the process of formation occurs at chain ends, as follows from studies on the structure and reactions of radical cations in freon matrices [5][6][7][8]. In the cited publications, it was found that the radical cations of linear alkanes in CFCI 3 and SF 6 matrices exhibited a planar extended zigzag structure ( transtrans conformers).…”
mentioning
confidence: 99%